The Effect of Exogenous Application of Chitosan in Beta Vulgaris (Beet) Drought Stressed Plants (Journal of Pharmaceutical Negative Results, 2022)
Background: In recent years, chitosan has been used to reduce salt stress. Chitosan is a biodegradable, nontoxic molecule. It can boost stress tolerance, aid physiological processes, and prevent transpiration-related water loss. beet cv. Rio Grande plants were treated with 0, 40, 80, or 100 mM salt. The plants' response to stress was mediated by chitosan at 0, 40, 80, or 100 mg L-1.Results: According to the findings, salt applications harmed almost all of the investigated criteria. Control beet were grown in salinity-free distilled water. Maximum plant height in centimeters, average number of compound leaves per plant, stem diameter in millimeters, number of fruits per plant, fruit firmness in kilograms per square centimeter, leaf chlorophyll content in micrograms per gram, fruit juice pH, yield per plant in kilograms, and minimum total soluble solids in degrees were recorded. Plants exposed to 100 mM salinity had the lowest plant height (in centimeters), lowest average number of compound leaves per plant, lowest stem diameter (in millimeters), lowest number of fruits per plant, lowest fruit firmness (in kilograms per square centimeter), lowest leaf chlorophyll content (in spades per acre), highest yield per plant (in kilograms), and highest TSS (in milligrams). Chitosan 150mgL-1 Maximum plant height (cm), average number of compound leaves plant-1, leaf area (cm2), stem diameter (mm), number of fruits plant-1, fruit firmness (kg cm-2), leaf chlorophyll content (SPAD), total soluble solids (Brix°).conclution plant-1 yield (kg) with minimal juice pH. 100mg/L chitosan 100mg/L chitosan 80 mg L-1 chitosan and 100 mM salt stress improve beet performance.